The Relationship Between Children Education in the Family and Car Driving and Motorcycle Riding Behaviour in Indonesia - Putranto, Leksmono Suryo; Alyandi, Yendi Fajar (International Journal of Integrated Engineering, 2019)
Children received their first-hand education from family environment. This paper is intended to evaluate whether children education in the family is related to car driver and motorcycle rider behaviour. Firstly, a long list of bad and good norms received from family revealed from ten respondents from various religions and ethnicities. 4 constructs (explanatory variables which are not directly observable) were found as Indonesian Family values (IFV), i.e. religious, disciplinary, ethical and politeness norms and law norms. Car driver behaviour was measured using Indonesian Driver Behaviour Questionnaire (IDBQ) consist of 4 constructs, i.e. aggressive behaviour, ordinary violation, errors, and lapses. Motorcycle rider behaviour was measured using Indonesian Motorcyle Behaviour Questionnaire (IMRBQ) consisted of 6 constructs, i.e. traffic/ control errors, speed/ safety/ traffic violations, and stunts. Pearson correlation analyses were conducted between means of each construct in IMRBQ, IDBQ and 4 constructs in IFV. Some of the constructs in IFV were significantly correlated with some constructs in MDBQ and IMRBQ.